Electronic and positronic studies of zinc-blend boron phosphide BP underpressure - Sehil, M.; Abid, H.; Lachebi, A. (Universiti Malaysia Perlis, 2009)
Link to publisher's homepage at http://www.unimap.edu.my/ ; Open access only applicable for vol. 1; issue 1, 2008 & vol. 2; issue 1, 2009.